Pemeriksaan Setempat (Local Inspection) dalam Sengketa Harta Bersama: Analisis Normatif Peran Hakim dalam Perspektif Asas Hakim Pasif - Salsabila Arza Risandra; Fathimah Syifa; Adinda Amirah Salsabila; Sri Handayani (CV. ITTC INDONESIA, 2026)
Marriage within the Indonesian legal system entails various legal consequences, one of which concerns the existence of marital property acquired during the marriage. In judicial practice, marital property disputes following a divorce often present complex evidentiary issues, especially when the objects of the dispute consist of immovable property such as land and buildings. These conditions require judges to obtain an accurate factual overview of the disputed objects, not only through conventional evidence but also through the mechanism of local inspection. The implementation of local inspection raises specific legal concerns when associated with the principle of judicial passivity in civil procedural law.This study uses a normative legal research method with a descriptive analytical approach through the examination of statutory regulations, doctrines, and relevant legal literature. The research findings indicate that local inspection is not positioned as formal evidence but rather as judicial knowledge that serves to complement and strengthen the assessment of evidence submitted by the parties. Within the context of the principle of judicial passivity, local inspection remains permissible as long as it does not exceed the limits of judicial authority, specifically by not shifting the burden of proof between the parties and not placing the judge in an active role to seek evidence for the interest of a single party. Consequently, local inspection plays an important role in the evidentiary process of marital property disputes, provided it is applied proportionally and in harmony with the principle of judicial passivity to ensure justice, legal certainty, and the utility of the judgment.